DOMINANSI, KERAGAMAN, DAN KEMERATAAN SPESIES TUMBUHAN BERKAYU DI AREA REKLAMASI PT ADARO INDONESIA - Erniawati Erniawati; Mochamad Arief Soendjoto; Asysyifa Asysyifa; Yudha Pahing Perdana (Jurnal Sylva Scienteae, 2020)
Revegetation with woody plants is a strategic effort to avoid the negative impacts of coal mining and at the same time improve the utilization of ex-mining land. This study aimed to analyze the dominance, diversity, and evenness of woody plant species planted in the reclamation area of PT. Adaro Indonesia. At 4 locations of reclamation area, paths consisting of 10 plots were made. In each plot (20 x 20) m, only 1 plot (10 x 10) m, only 1 plot (5 x 5) m, and only 1 plot (2 x 2) m were successively made. The plot (20 x 20) m was used to record tree level, (10 x 10) m for the pole level, (5 x 5) m for the sapling level, and (2 x 2) m for the seedling level. Dominance was determined by important value index, while diversity and evenness were based on the Shannon index. Fourteen of the 21 woody plant species were intentionally planted and the remaining 7 species grew spontaneously. Of the 14 species, 64.29% were legumes and 35.71% non-legumes. The dominance, diversity and evenness vary according to their level of growth and location. The highest species diversity does not always coincide with the highest species evenness.Keywords: diversity, dominancy, evenness, reclamation area, woody plant